Developing with PDF - Rosenthol, Leonard (O'Reilly, 2013)
PDF is becoming the standard for digital documents worldwide, but it's not easy to learn on your own. With capabilities that let you use a variety of images and text, embed audio and video, and provide links and navigation, there's a lot to explore. This practical guide helps you understand how to work with PDF to construct your own documents, troubleshoot problems, and even build your own tools. You'll also find best practices for producing, manipulating, and consuming PDF documents. In addition, this highly approachable reference will help you navigate the official (and complex) ISO documentation. Learn how to combine PDF objects into a cohesive wholeUse PDF's imaging model to create vector and raster graphicsIntegrate text, and become familiar with fonts and glyphsProvide navigation within and between documentsUse annotations to overlay or incorporate additional contentBuild interactive forms with the Widget annotationEmbed related files such as multimedia, 3D content, and XML filesUse optional content to enable non-printing graphicsTag content with HTML-like structures, including paragraphs and tables.